Integrasi Strategi Value Clarification Technique (VCT) dalam Materi Akhlak Madzmumah untuk Mengembangkan Etika Digital dan Self-Control Siswa - ‘Ainul Mardhiyyah; Hafid Muslih; Siti Sutiawati; Silma Mazia Effendi; Rijalul Haq; Khairuddin Manurung (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
Abstract: The rapid advancement of digital technology has created new moral challenges for high school students, particularly in the form of unethical digital behavior such as cyberbullying, hate speech, and the spread of harmful content behaviors that fundamentally reflect the Islamic concept of akhlak madzmumah (reprehensible morality). However, existing PAI (Islamic Religious Education) instruction continues to address this subject through conventional lecture-based methods that fail to develop students' digital ethics or self-control. This study aims to analyze the integration of the Value Clarification Technique (VCT) strategy within akhlak madzmumah material as a means of developing high school students' digital ethics and self-control. Using a qualitative approach through library research (library research), data were collected from accredited academic journals, official PAI textbooks, and related literature published between 2021–2026, then analyzed using interactive content analysis following the Miles, Huberman, and Saldana model. The findings reveal that concepts such as israf, riya, sum'ah, takabur, and hasad have direct digital equivalents including doomscrolling, flexing, oversharing, cancel culture, and hate comments. The three stages of VCT choosing, prizing, and acting are highly relevant for guiding students through moral reflection on these digital dilemmas, fostering value internalization, and strengthening self-regulation in digital spaces. This study concludes that VCT-based learning of akhlak madzmumah offers an innovative and contextually grounded model for Islamic moral education in the digital age. Keywords: Value Clarification Technique, Akhlak Madzmumah, Digital Ethics, Self-Control, Islamic Religious Education Abstrak : Pesatnya perkembangan teknologi digital memunculkan tantangan moral baru bagi siswa SMA, khususnya dalam bentuk perilaku negatif di ruang siber seperti cyberbullying, hate speech, dan penyebaran konten merugikan yang pada hakikatnya merupakan manifestasi kontemporer dari akhlak madzmumah. Namun, pembelajaran PAI selama ini masih menyampaikan materi tersebut secara normatif-kognitif melalui metode ceramah konvensional yang belum mampu membentuk etika digital maupun self-control siswa. Penelitian ini bertujuan menganalisis integrasi strategi Value Clarification Technique (VCT) dalam materi akhlak madzmumah untuk mengembangkan etika digital dan self-control siswa SMA. Menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research), data dikumpulkan dari jurnal akademik terakreditasi, buku teks PAI resmi, dan literatur relevan terbitan 2021-2026, kemudian dianalisis menggunakan analisis isi interaktif model Miles, Huberman, dan Saldana. Hasil penelitian menunjukkan bahwa konsep israf, riya, sum'ah, takabur, dan hasad memiliki ekuivalen digital yang spesifik, meliputi doomscrolling, flexing, oversharing, cancel culture, dan hate comment. Ketiga tahapan VCT choosing, prizing, dan acting terbukti relevan dalam memandu siswa merefleksikan dilema moral digital, menginternalisasi nilai, dan memperkuat regulasi diri di ruang siber. Penelitian ini menyimpulkan bahwa pembelajaran akhlak madzmumah berbasis VCT merupakan model inovatif dan kontekstual bagi pendidikan moral Islam di era digital. Kata Kunci: Value Clarification Technique, Akhlak Madzmumah, Etika Digital, Self-Control, Pendidikan Agama Islam